Clinical profile of patients presenting with inhalational organophosphorus poisoning in central India: a retrospective study - Divekar, Sachin; Bhelkar, Sandeep M.; Hiwarkar, Prabhakar; Masare, Monika (International Journal Of Community Medicine And Public Health, 2020)
Background: World Health Organisation (WHO) report through International Programme on Chemical Safety (IPCS), poisoning is a significant global public health problem. According to WHO data, in 2012 an estimated 193,460 people died worldwide from unintentional poisoning. Intentional and unintentional pesticide poisoning has been acknowledged as a serious problem in many countries, including India, Limited literature available on clinical profile of organophosphorus poisoning cases, with this background present study was attempted. Objective of the study was to know the clinical presentation of OP poisoning cases admitted in tertiary care hospital. Methods: A retrospective record based observational study was conducted. Results: A total of 535 patients presented in the emergency department with the clinical features of OP poisoning. Mean age of the persons presenting in the emergency was 33.3±10.1 years. Nausea and vomiting is the most commoner symptom reported by 60.7% of patients followed by giddinesss (41.3%), loose motion (28.2%) and secretions (9.5%). Signs like abnormal pupil size, fasciculations and inability to neck holding were common with 23.55% 19.3% and 21.1% respectively. Statistical significance was found between Serum acetylcholine esterase level and outcome of patients (p<0.01). 96.1% received treatment less than half an hours. 18 patients required ventilator and among these 13 were died. Conclusions: Majority of the patients were of young age with males outnumbering females. Nausea and vomiting was the most common symptom reported by the patients while abnormal pupil size was the most common sign observed at the emergency department.